2011
DOI: 10.1007/978-3-642-23822-2_31
|View full text |Cite
|
Sign up to set email alerts
|

A New RFID Privacy Model

Abstract: Abstract. This paper critically examines some recently proposed RFID privacy models. It shows that some models suffer from weaknesses such as insufficient generality and unrealistic assumptions regarding the adversary's ability to corrupt tags. We propose a new RFID privacy model that is based on the notion of indistinguishability and that does not suffer from the identified drawbacks. We demonstrate the easy applicability of our model by applying it to multiple existing RFID protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 27 publications
1
85
0
Order By: Relevance
“…We have further shown that IND-CCA security alone could fail to reach this level of privacy. This shows a separation between our privacy model and the one from [22]. However, the question whether this separation is significant remains open.…”
Section: Resultsmentioning
confidence: 74%
“…We have further shown that IND-CCA security alone could fail to reach this level of privacy. This shows a separation between our privacy model and the one from [22]. However, the question whether this separation is significant remains open.…”
Section: Resultsmentioning
confidence: 74%
“…People already suggested to protect location privacy [33], but this suffers from severe limitations as shown in [1,27]. Anonymity could also be considered in a way similar to RFID protocols [37,32,23]. One proposal is made in [22] but without terrorist fraud protection.…”
Section: Resultsmentioning
confidence: 99%
“…The most general and prominent model for privacy is the simulation-based privacy notion in [17] which was enriched in [15]. Hermans et al [14] presented a simpler privacy model which we call the HPVP model. [14] Distance Hijacking.…”
Section: Definition 2 ([18]) We Consider the Following Honest-provermentioning
confidence: 99%
“…Hermans et al [14] presented a simpler privacy model which we call the HPVP model. [14] Distance Hijacking. In distance hijacking [7], the prover is malicious, running an algorithm A and we add a honest prover P(sk P ′ , pk V ) with another identity P ′ associated to pk P ′ .…”
Section: Definition 2 ([18]) We Consider the Following Honest-provermentioning
confidence: 99%